Consistency of recommendations of clinical practice guidelines in periodontology: a systematic review - Marco Antonio ALARCÓN; Tania ARIZA-FREITAS; Natali CHAVEZ-VEREAU; Andrea LÓPEZ-PACHECO; Claudio Mendes PANNUTI; Lilian MÁLAGA-FIGUEROA (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The aim of this systematic review was to evaluate the methodological quality and the consistency of recommendations of clinical practice guidelines (CPGs) in Periodontology. An electronic search was conducted in two databases, MEDLINE and EMBASE, eight CPGs databases, and home pages of scientific societies in Periodontology up to April 2022. Three reviewers independently assessed methodological quality using the AGREE II instrument. In addition, we evaluated the consistency of the recommendations. Eleven CPGs were included, and the topics developed focused on prevention, diagnosis, risk factors, surgical and non-surgical periodontal treatment, antimicrobial therapy, root coverage, and maintenance. We found that the AGREE domains 2 (Stakeholder involvement) and 5 (Applicability) obtained the lowest scores. Domains 1 (Scope and purpose), 3 (Rigor of development) and 4 (Clarity of presentation) obtained the highest scores among the evaluated CPGs. The clinical recommendations for treatment of periodontal diseases were mostly consistent. Overall, the quality of CPGs used in periodontics was high. There was consistency of recommendations in specific fields. These findings may help researchers to promote CPGs focused on different fields of periodontics that have not yet been developed. Furthermore, the clinician will be able to make better clinical decisions.